Challenges of controlling a large outbreak of OXA-48 carbapenemase-producing Klebsiella pneumoniae in a French university hospital. Issue 4 (April 2015) - Semin-Pelletier, B.; Cazet, L.; Bourigault, C.; Juvin, M.E.; Boutoille, D.; Raffi, F.; Hourmant, M.; Blancho, G.; Agard, C.; Connault, J.; Corvec, S.; Caillon, J.; et al.
Summary A large outbreak of OXA-48 carbapenemase-producing Klebsiella pneumoniae at Nantes University Hospital was investigated. The index case had no history of travel or hospitalization abroad and had been hospitalized in the internal medicine department for more than one month when the epidemic strain was isolated from a urine sample in June 2013. Seventy-two secondary cases were detected by weekly screening for gastrointestinal colonization during the two phases of the outbreak from June to October 2013 (33 cases) and from November 2013 to August 2014 (39 cases). Spread of the epidemic strain was attributed to the proximity of, and staff movement between, the infectious diseases (32 cases) and the internal medicine (26 cases) departments; 14 secondary cases were also observed in the renal transplant department following the transfer of an exposed patient from the infectious diseases department. Most of the patients (90%) were colonized and no death was linked to the epidemic strain. More than 3000 contact patients were reviewed and 6000 rectal swabs were performed. Initial control measures failed to control the outbreak owing to the late detection of the index case. The late implementation of three successive cohort units, the large number of transfers between wards, and the frequent readmission of cases contributed to the incomplete success of control measures.